Energy Harvesting: Flexible Porous Piezoelectric Cantilever on a Pacemaker Lead for Compact Energy Harvesting (Adv. Mater. Technol. 1/2019). Issue 1 (8th January 2019) - Dong, Lin; Han, Xiaomin; Xu, Zhe; Closson, Andrew B.; Liu, Yin; Wen, Chunsheng; Liu, Xi; Escobar, Gladys Patricia; Oglesby, Meagan; Feldman, Marc; Chen, Zi; Zhang, John X. J.
Abstract : In article number1800148, Lin Dong, Zi Chen, John X. J. Zhang, and co‐workers develop a compact, modular and compliant thin film energy harvester on a cardiac pacemaker lead which converts mechanical motion to electrical power. The device could enable self‐charging batteries to ultimately power pacemakers and other implantable biomedical devices. It provides a new paradigm for biomedical energy harvesting in vivo.